Does competition have a relationship with efficiency and productivity? - EK˙IN AKDEN˙IZ (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this research is to determine whether or not there is a correlation between the level of competition in a given competition and the level of efficiency or productivity achieved by that market. With this in mind, the study’s primary objective is to determine whether or not intense competition affects efficiency and productivity.Method: The current investigation takes a descriptive approach to its presentation of data. Information was gathered from books and articles already published. The findings were derived from a comparative analysis.Findings: When competition is healthy, the market sends firms clear signals (such as the prices they can charge and the profits they can earn) about the goods and services consumers want to purchase. Therefore, it can be said that competitiveness is linked to effectiveness and output.Implications/Novel Contribution: The importance of the study is articulated through the connection between the three concepts of competition, efficiency, and productivity, which are not fully developed in the papers cited in the literature review. The presented relationship with the existing literature review can be dealt with in future studies, and unfavorable aspects of the relationship can also be embraced.